I territori della contemporaneità Percorsi di ricerca nella multidisciplinarietà - Rossi, Maddalena; SARAGOSA, CLAUDIO (Territori, 2018)
This text collects the revisions of some of the most significant degree theses written from 2011 to 2015 in the bachelor degree in City, territory and landscape planning and in the Master's degree in City and territory planning and design of University of Florence, Empoli campus. The theses cover the current diversified scenery of problems within the urban planning discipline, using very different methodologies, interpretations and perspectives of analysis. The territory emerging as the protagonist of the young authors' narratives is a complex and multi-layered object; it is constituted by things and relationships, set on the long times of history, aimed towards the present and projected into the future, and it continues to raise their questions, doubts, curiosities and also some fruitful answers. In summary, rather than chances for discussion on a disposable form of knowledge, this works offer chances for reflection and experimentation, and opportunities for the incremental construction of creative solutions by its authors.